(3LGeY GdHjGf Yf JChjd Bi GdaQbGfs - (3eMeO Hf LQjQ Hf jRjO GdWHQj , GHf LQjQ, CHh LYaQ, J (B310 (3g` s ((3YHO GdQMf Hf gGQhf s)
(3ChdgG (B:s
(3hChd eG ajg CKfGA JaSjQ GdBjI GdcQjeI (B" (3SJYPHge eQJjf Ke jQhf Edi YPGH YXje (B" (3Hbhdg (B: (3MOKfG HTQ SfgPHge eQJjf YPGH GdfGQ hYPGH GdbHQ s
(3BNQgG (B:s
(3jfJgi HBNQ ShQI GdJhHI HGdbhd ai JChjd bhdg JYGdi (B" (3aEf JhdhG abd MSHi Gddg dG Edg EdGgh (B" (3Yf CHj Hf cYH bGd CMOK GdbQBf YgOkG HGddg GdBjJGf dbO LGAce QShd ef CfaSce Edi BNQ GdShQI s
(3bWYI JTJe dY JaSjQ ChGNQ ShQI GdJhjIs
(3fSNI Ydi Qb ZRGds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B69 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B147s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdJaSjQ hYdhe GdbQBfs